2015
DOI: 10.1097/rhu.0000000000000297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antituberculous Drugs on Serum Uric Acid and Urine Uric Acid Excretion

Abstract: The hyperuricemic effect of pyrazinamide and ethambutol was due primarily to a decrease in UACl, which was reversible, and had no negative effect on the renal function. Arthralgia was uncommon and required no specific treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The level of SUA is closely related to the renal excretion of uric acid. Besides, pathological change, diet, gene mutation or medicine effects may affect the excretion of uric acid [13][14][15][16]. A number of studies have shown that reduction of uric acid excretion is harmful to various systems [17], while some recent studies have demonstrated that increased uric acid excretion may be one of the causes of acute and chronic kidney disease as well.…”
Section: Discussionmentioning
confidence: 99%
“…The level of SUA is closely related to the renal excretion of uric acid. Besides, pathological change, diet, gene mutation or medicine effects may affect the excretion of uric acid [13][14][15][16]. A number of studies have shown that reduction of uric acid excretion is harmful to various systems [17], while some recent studies have demonstrated that increased uric acid excretion may be one of the causes of acute and chronic kidney disease as well.…”
Section: Discussionmentioning
confidence: 99%
“…As is stated before, anti‐TB treatment can result in liver injury through four mechanisms 3 . As for uric acid levels, all patients enrolled were treated with INH, RIF, PZA, and EMB, in which INH, PZA, EMB, and their metabolites could compete with uric acid for the organic acid excretion pathway, reducing the excretion of uric acid, thus causing the increase of uric acid y 67 . In this study, a statistical significance on the relationship between mutant homozygote AA and total protein was found.…”
Section: Discussionmentioning
confidence: 99%
“…These are considered as committed markers of nephritic injury and suggest the loss of a major part of kidney function . These anti‐TB drugs also lead to elevation of cholesterol, which can be due to deposition of fat in the liver, latter develops either due to lipids oversupply or interference with lipid accumulation mechanisms . There is a strong link between hypercholesterolaemia and increased free radical production.…”
Section: Discussionmentioning
confidence: 99%
“…24 These anti-TB drugs also lead to elevation of cholesterol, which can be due to deposition of fat in the liver, latter develops either due to lipids oversupply or interference with lipid accumulation mechanisms. 25,26 There is a strong link between hypercholesterolaemia and increased free radical production. During oxidative stress, ROS are produced, which react with lipoproteins to generate their oxidation states, consequently cellular absorption of lipids from the blood is decreased.…”
Section: Discussionmentioning
confidence: 99%